1996
DOI: 10.1016/s0022-5347(01)65419-3
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Guidelines Panel on Erectile Dysfunction: Summary Report on the Treatment of Organic Erectile Dysfunction

Abstract: For the standard patient, defined as a man with acquired organic erectile dysfunction and no evidence of hypogonadism or hyperprolactinemia, the panel recommends 3 treatment alternatives: vacuum constriction devices, vasoactive drug injection therapy and penile prosthesis implantation. Based on the data to date, yohimbine does not appear to be effective for organic erectile dysfunction and, thus, it should not be recommended as treatment for the standard patient. Venous surgery and arterial surgery in men with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
88
1
14

Year Published

1997
1997
2011
2011

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 196 publications
(104 citation statements)
references
References 3 publications
1
88
1
14
Order By: Relevance
“…1 Two effective medical treatments for ED of various aetiologies include intracavernosal (IC) injection therapy with vasoactive agents (eg, prostaglandin E 1 (PGE 1 ), papaverine, and phentolamine) 2,3 and oral therapy with phosphodiesterase type 5 inhibitors, sildenafil citrate (VIAGRA s ) being the first in the class. 4,5 Despite its efficacy, IC PGE 1 therapy is associated with patient-initiated discontinuation rates as high as 60%.…”
Section: Introductionmentioning
confidence: 99%
“…1 Two effective medical treatments for ED of various aetiologies include intracavernosal (IC) injection therapy with vasoactive agents (eg, prostaglandin E 1 (PGE 1 ), papaverine, and phentolamine) 2,3 and oral therapy with phosphodiesterase type 5 inhibitors, sildenafil citrate (VIAGRA s ) being the first in the class. 4,5 Despite its efficacy, IC PGE 1 therapy is associated with patient-initiated discontinuation rates as high as 60%.…”
Section: Introductionmentioning
confidence: 99%
“…4 The recent meeting of the International Society for Impotence Research afforded an opportunity to record the more important new therapies and these have been included where possible. Other signi®cant therapies, widely known to be in development or reported at meetings were also considered.…”
Section: Methodsmentioning
confidence: 99%
“…They can be listed individually with good con®dence that their characteristics are identi®able and their actions selfexplanatory. 4 However, the speci®c mechanisms of action that underlie these therapies were not fully understood. Interestingly subsequent research has shown that some of the early concepts used to explain the effect of different agents were almost visionary in their insight.…”
Section: Introductionmentioning
confidence: 99%
“…9 Currently recommended therapies for ED are limited and include intracorporal injection of vasoactive substances alone or in combination (papaverine, phentolamine, prostaglandin E1), 10 transurethral delivery of alprostadil, 11 vacuum devices, and prosthetic implantation. 12 All are associated with considerable limitations, including inconvenience, lack of spontaneity, poor toleration, and partial or restricted efficacy. These constraints manifest as reduced patient acceptability and compliance.…”
Section: Introductionmentioning
confidence: 99%